Targeting the human epidermal growth factor receptor 2 (HER2) oncogene in colorectal cancer. (6th April 2018) - Siena, S; Sartore-Bianchi, A; Marsoni, S; Hurwitz, H I; McCall, S J; Penault-Llorca, F; Srock, S; Bardelli, A; Trusolino, L
Abstract: Human epidermal growth factor receptor 2 ( HER2 ) is an oncogenic driver, and a well-established therapeutic target in breast and gastric cancers. Using functional and genomic analyses of patient-derived xenografts, we previously showed that a subset (approximately 5%) of metastatic colorectal cancer (CRC) tumors is driven by amplification or mutation of HER2 . This paper reviews the role of HER2 amplification as an oncogenic driver, a prognostic and predictive biomarker, and a clinically actionable target in CRC, considering the specifics of HER2 testing in this tumor type. While the role of HER2 as a biomarker for prognosis in CRC remains uncertain, its relevance as a therapeutic target has been established. Indeed, independent studies documented substantial clinical benefit in patients treated with biomarker-driven HER2-targeted therapies, with an impact on response rates and duration of response that compared favorably with immunotherapy and other examples of precision oncology. HER2-targeted therapeutic strategies have the potential to change the treatment paradigm for a clinically relevant subgroup of metastatic CRC patients.